Parking in Lisbon - Gomes, Maria do Carmo Leal da Silva (2019)
The parking market is characterized by two types of distortions: crusing and local market power. This thesis studies the determinants of parking facilities’ prices in Lisbon using a cross-sectional database for facilities in the city, and how this can be influenced by curbside parking fees. The results show that operational costs drivers like having for instance a bathroom impact prices the most, but local market power and curbside parking density within a 500meters buffer also correlate with prices, negatively, as a unitary increase of each leads to a decrease in price of 0.4352% and 0.0001%, respectively.